Salinity Tolerance in Chickpea Genotypes during Germination - POLICEPATIL, BASAVARAJESHWARI; DODDAGOUDAR, SR; GOWDA, BASAVE; MACHA, SANGEETA I; LAKSHMIKANTH; LAXUMAN (Seed Research, 2026)
A laboratory experiment for screening 25 chickpea genotypes collection from Zonal Agricultural Research Station (ZARS), Kalaburgi and from ICRISAT along with one susceptible (ICCV 96836) and one tolerant check (JG-14) for salinity tolerance was carried out at the Department of Seed Science and Technology, College of Agriculture, University of Agricultural Sciences, Raichur in a two factorial completely randomized design, with four replications. The first experiment consisted of two salinity levels viz., 0 mM NaCl (S1) and 30 mM NaCl (S2) as factor-I and 25 chickpea genotypes (G1 to G25) as factor-II. The second experiment was conducted to assess the performance (tolerance level) of five best identified genotypes from experiment I based on seed germination at higher salinity levels (up to 120 mM NaCl). The experimental results revealed that out of 25 screened genotypes in the first experiment, five genotypes, viz., BGD-103, ICCV-4958, WR-315, KCS-2 and KCS-4 recorded ignificantly higher seed germination (97.3 , 98 , 99.8, 98 and 99 per cent, respectively) and vigour (3115, 3220, 3555, 3061 and 3126, respectively) which were found tolerant to salinity stress at 30 mM NaCl stress level. These screened genotypes were further subjected for reconfirmation for their tolerance at 30 mM and also were checked for their performance under higher salinity levels (up to 120 mM) in the second experiment. The results revealed that with the increasing salinity levels, the seed germination and seedling vigour of all the chickpea genotypes decreased. Among the five genotypes, WR-315 recorded significantly higher seed germination (99.2 %) and seedling vigour index (2957) even up to 120 mM salinity level. Salinity adversely affects the seed germination and seedling establishment of chickpea. Among the 25 genotypes, BGD-103, ICCV-4958, WR-315, KCS-2 and KCS-4 were found tolerant upto 30 mM NaCl while the genotype, WR-315 was tolerant even at higher salinity level (120 mM NaCl). The study depicts that the genotypes BGD-103, ICCV-4958, WR-315, KCS-2 and KCS-4 can be used where the soil salinity is upto 30 mM NaCl while the genotype, WR-315 can be used where the salinity is up to120 mM NaCl.